Rainfall runoff measuring methods. - Mohd Soom, Mohd Amin; Mahmood, Waleed Abdulrashid; Ghazali, Abdul Halim; Mohd Shariff, Abdul Rashid; Wayayok, Aimrun; Mosleh, Mogeeb A. A. (2009)

(untitled)
The present technique relates to a method of measuring rainfall runoff. The method includes deriving rainfall data for estimating rainfall by radar using at least one radar station. Moreover, the method develops a rainfall calibration model for at least one radar station using radar derived rainfall data. In particular, the method identifies at least one rain gauge station of at least one radar station for developing the rainfall calibrating model. In addition, the method includes comparing recorded data of at least one rain gauge station with rainfall data of the radar. Additionally, the method estimates the measurement of the rainfall runoff using the recorded data of at least one rain gauge station and the rainfall data of the radar.